Guyton and Hall textbook of medical physiology - Hall, John E. (John Edward), 1946- (Philadelphia, PA : Elsevier, 2016)
The 13th edition of Guyton and Hall Textbook of Medical Physiology continues this bestselling title's long tradition as the world's foremost medical physiology textbook. Unlike other textbooks on this topic, this clear and comprehensive guide has a consistent, single-author voice and focuses on the content most relevant to clinical and pre-clinical students. The detailed but lucid text is complemented by didactic illustrations that summarize key concepts in physiology and pathophysiology.
Introduction to physiology: the cell and general physiology -- Membrane physiology, nerve, and muscle -- The heart -- The circulation -- The body fluids and kidneys -- Blood cells, immunity, and blood coagulation -- Respiration -- Aviation, space, and deep-sea diving physiology -- The nervous system: A. General principles and sensory physiology -- The nervous system: B. The special senses -- The nervous system: C. Motor and integrative neurophysiology -- Gastrointestinal physiology -- Metabolism and temperature regulation -- Endocrinology and reproduction -- Sports physiology.
Includes bibliographical references.
Online resource; title from electronic title page (ClinicalKey, viewed on July 20, 2015).
Keywords: Human physiology; Physiology, Pathological; Human physiology; Physiology, Pathological; Physiological Phenomena; Electronic books